Phylogenetic Relationships Between and Within 11 Taxa of Genus Vicia from Algeria Based on Evidence from Isozymes and Physical Seed Properties - Bechkri, Sakina; Medoukali, Imane; Khelif, Douadi (European Scientific Journal, ESJ, 2017)
Isozyme patterns for aspartate amino transferase, alcohol dehydrogenase and superoxide dismutase were evaluated in 60 accessions of eleven Vicia taxa occurring in Algeria. The three enzymatic systems revealed 25 morphs of different frequency encoded by 7 loci. Similarity between species and accessions was estimated by Euclidean distances based on presence or absence of bands. The UPGMA method was utilized for the groupings and dendrogram construction. The dendrogram presented 2 major groups, each one corresponding to a taxonomic level where accessions of the same species grouped together. Taxa-specific bands were identified. In parallel, 12 physical seed properties namely: length, width, thickness, arithmetic diameter, geometric diameter, sphericity, surface area, volume, square mean diameter, equivalent diameter, seed aspect ratio and 1000 seed weight were calculated. By cluster analyses based upon them, the material has been classified into 2 major groups with no correspondence with the current taxonomy. A Principal Component Analysis was undertaken to distinguish physical properties which contribute the most to accessions distinction. Mantel test was used to assess correlation between the three enzymatic systems studied one side and between enzymes polymorphism and physical seed properties another side.